She walks in beauty - Kennedy, Caroline 1957-; Kennedy, Caroline 1957-; Kennedy, Caroline 1957-; Alexander, Jane 1939-; Lloyd, John Bedford; Davis, Hope 1964-; Scott, Campbell 1961- (Hyperion Audio, 2011)
"She Walks in Beauty" is Kennedy's selection of poetry that tells the story of a woman's life, including first love and lasting love; marriage, motherhood, and work; times of silence and solitude, and times of awe. The collection includes works by Elizabeth Bishop, Sharon Olds, Edna St. Vincent Millay, Mary Oliver, Pablo Neruda, W.H. Auden, Adrienne Rich, Sandra Cisneros, Anne Sexton, W.S. Merwin, Dorothy Parker, Queen Elizabeth I, Lucille Clifton, Naomi Shihab Nye, and W.B. Yeats